2022
DOI: 10.1155/2022/3546795
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] LINC00518 Promotes Cell Malignant Behaviors via Influencing EIF4A3‐Mediated mRNA Stability of MITF in Melanoma

Abstract: Melanoma has become the most severe sort of skin cancer, deriving from the pigment-producing melanocytes. Existing research has validated that long noncoding RNAs (lncRNAs) have critical function in the progression of cancers. LINC00518 has been studied in cutaneous melanoma; however, the molecular mechanism of LINC00518 in melanoma needs in-depth investigation. In our study, LINC00518 was revealed to be upregulated in melanoma tissues and cells, and melanoma patients in high LINC00518 expression group had poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In uveal melanoma, LINC00518 acts as an oncogene, and transient silencing of LINC00518 in vitro affects cell proliferation and migration [35]. LINC00518 promotes malignant behaviors by influencing EIF4A3-mediated MITF mRNA stability [36], and the miR-204-5p/AP1S2 axis promotes the metastasis of malignant melanoma [37]. Knockdown of LINC00518 in cutaneous malignant melanoma cells significantly inhibited cell invasion, migration, proliferation, and clonogenicity [38].…”
Section: Discussionmentioning
confidence: 99%
“…In uveal melanoma, LINC00518 acts as an oncogene, and transient silencing of LINC00518 in vitro affects cell proliferation and migration [35]. LINC00518 promotes malignant behaviors by influencing EIF4A3-mediated MITF mRNA stability [36], and the miR-204-5p/AP1S2 axis promotes the metastasis of malignant melanoma [37]. Knockdown of LINC00518 in cutaneous malignant melanoma cells significantly inhibited cell invasion, migration, proliferation, and clonogenicity [38].…”
Section: Discussionmentioning
confidence: 99%
“…In several types of cancer, most lncRNAs are either up- or downregulated. These lncRNAs favor all stages of tumor development through the promotion of mRNA expression and constancy [ 253 ], by favoring mRNA stability [ 254 ], or by modulating miR [ 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 ]. The aberrant phenotype is the result of the modulation of typical pathways playing key roles in cell survival [ 255 , 259 , 263 , 265 , 283 ], apoptosis [ <...…”
Section: Analyzing Cernets For Diagnosis and Targeting Them For Thera...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%